UPLC-ESI-QTOF-MS phenolic compounds identification and quantification from ethanolic extract of Myrtus communis ‘Variegatha’: In vitro antioxidant and antidiabetic potentials - Kunle Okaiyeto; Nasifu Kerebba; Fanie Rautenbach; Sachin Kumar Singh; Kamal Dua; Oluwafemi O. Oguntibeju (Arabian Journal of Chemistry, 2023)
Global public health is seriously threatened by diabetes and its complications. Although several synthetic drugs are currently employed for managing diabetes, however, the adverse effects associated with their use cannot be underestimated. Thus, the quest for a safe and cost-effective alternative is highly imperative. In the present study, the phenolic contents, antioxidant, antidiabetic, and cytotoxic potentials of 70% ethanolic crude extract of Myrtus communis ‘Variegatha’ were investigated using in vitro biochemical protocols. The total polyphenols content was 116.44 mg GAE/g, flavonols (6.74 mg QE/g), flavanols (2.46 mg CE/g) and the ferric reducing antioxidant power (FRAP) value was 1267.28 µmol AAE/g, 2,2-diphenyl-1-picrylhydrazyl (DPPH) (1165.37 µmol TE/g), and Trolox equivalent antioxidant capacity (TEAC) (775.52 µmol TE/g). High-resolution ultra-performance liquid chromatography coupled with electrospray ionisation/quadrupole-time-of-flight-mass spectrometry (UPLC-ESI-QTOF-MS) was explored to identify the phenolic compounds, most of which were flavonoids. The extract demonstrated a strong α-glucosidase inhibition potential in a concentration-dependent manner with IC50 (3.159 µg/mL), which was higher than epigallocatechin gallate (EGCG) (6.208 µg/mL), a positive control antidiabetic drug. A slight increase in glucose utilization was observed after 24 h of treatment in C3A hepatocytes at 25 μg/mL whereas an increase in glucose uptake was recorded at 25 and 50 μg/mL. The extract exhibited a cytotoxic effect (IC50 76.85 µg/mL) against C3A hepatocytes at 100 µg/mL, which correlates to the glucose utilization and uptake recorded. The findings from the study show the prospect of M. communis ‘Variegatha’ as a promising source of bioactive compounds that could be used in the development of new anti-diabetic agents, thus, further research into the plant is recommended.